1981
DOI: 10.1111/j.1600-0714.1981.tb01244.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased numbers of mast cells in the hyperplastic buccal mucosa of the zinc‐deficient rat

Abstract: Six weanling male Sprague Dawley rats were fed a diet eontaining 0.4 ppm Zn and seven were fed an identieal diet exeept for 40 ppm Zn. After 4 weeks, speeimens of bueeal mueosa in the region faeing the molar teeth were removed. Paraffin seetions, eut at 6 ^m, were stained with toluidine blue, and traeings made of five seetions per animal, spaeed no less than 60 pim apart. Counts of mast eells over a measured length of seetion were made in a superfieial zone of the lamina propria of 50 ^m width and a deeper zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
2
0
0
Order By: Relevance
“…Having used an alkaline phosphatase technique for visualizing capillaries, we may summarize the main finding in the present series of zinc-deficient rats as demonstrating an increase in the size of the capillary bed available to the buccal epithelium, and associated increases in epithelial dimensions, as specified below. Confirming findings of previous series (Alvares & Meyer 1973, Meyer & Alvares 1974, Chen et al 1975, we observed complete conversion to parakeratosis, increased prominence of mitoses and hypertrophic spinous and granular cells in the epithelium, numerous mast cells and absence of inflammatory changes in the lamina propria (Kravich et al 1980). As to the capillaries, frequent qualitative changes can be described as "coiled, elongated and widened", which is the same triad of terms used by Braun-Falco & Burg (1970) to characterize capillaries in less severely inflamed psoriatic lesions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Having used an alkaline phosphatase technique for visualizing capillaries, we may summarize the main finding in the present series of zinc-deficient rats as demonstrating an increase in the size of the capillary bed available to the buccal epithelium, and associated increases in epithelial dimensions, as specified below. Confirming findings of previous series (Alvares & Meyer 1973, Meyer & Alvares 1974, Chen et al 1975, we observed complete conversion to parakeratosis, increased prominence of mitoses and hypertrophic spinous and granular cells in the epithelium, numerous mast cells and absence of inflammatory changes in the lamina propria (Kravich et al 1980). As to the capillaries, frequent qualitative changes can be described as "coiled, elongated and widened", which is the same triad of terms used by Braun-Falco & Burg (1970) to characterize capillaries in less severely inflamed psoriatic lesions.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, changes over a 2-3 mm stretch of sections in both chief planes were measured. In another series (Kravich et al 1980), the increase in the region of the occlusal plane, where thickening is maximal, was nearly identical to the present one for the cell layer, but the keratin layer showed 3.86 fold thickening.…”
Section: Discussionsupporting
confidence: 85%